Nexus between Principals’ Instructional Responsibilities and Secondary School Effectiveness - Adeseko Sunday Olaifa; Omotayo Adewale Awodiji (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
Success in school is attributed to regular evaluation of teaching and learning, an emphasis on professional growth, and a positive learning environment. This study investigated the correlation between school effectiveness and principals’ instructional responsibilities. A correlational design of post-positivism was adopted in this study. All 7059 teachers employed by the 347 public senior secondary schools in Kwara State, Nigeria, made up the study's population. A systematic sampling technique was used to select 558 participants. Five hundred and fifty-eight participants were chosen using a systematic sampling method. The findings show a significant nexus between principals’ instructional responsibilities and the effectiveness of secondary schools. Therefore, it recommends that to enhance school effectiveness, principals should be provided with induction courses at their appointment as principals to acquaint them with relevant knowledge on the importance of instructional responsibilities.